2013
DOI: 10.1182/blood-2013-04-497875
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived acute myeloid leukemia in a kidney transplant recipient

Abstract: volume was 77 mL/kg, twice the laboratory's top normal range in women (28 mL/kg). Serum erythropoietin level was repeated and was found to have decreased below normal at 3.0 mU/mL. A diagnosis of PV was made, and a therapeutic phlebotomy was initiated.To date, the patient has undergone 38 therapeutic phlebotomies during a 6-year period, and the patient continues with elevated hemoglobin concentrations and platelet counts. Her symptoms are well controlled, although she continues to have splenomegaly according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…As opposed to previous reports of leukemia after solid organ transplantation, this report demonstrates leukemic involvement of only the transplanted organs [ 4 6 ]. We believe that these cases may be the first reported cases of donor transmitted renal-limited myeloid sarcoma to two recipients from the same deceased organ donor.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…As opposed to previous reports of leukemia after solid organ transplantation, this report demonstrates leukemic involvement of only the transplanted organs [ 4 6 ]. We believe that these cases may be the first reported cases of donor transmitted renal-limited myeloid sarcoma to two recipients from the same deceased organ donor.…”
Section: Discussioncontrasting
confidence: 92%
“…This report describes the rare development of donor-derived myeloid sarcoma in two kidney transplant recipients from a single donor. Donor-derived leukemia has been reported after solid organ transplantation in liver transplant recipients and in a renal transplant recipient [ 4 6 ]. In these cases, the authors hypothesized that the most likely mechanism of disease was transformation of normal hematopoietic stem cells residing in the allograft into a malignant clone following transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small study using fucosylation of UCB cells has shown engraftment in 14 days 22 . The combination of haploidentical with either a single or double UCBT has been shown to improve engraftment 23 25 .…”
Section: New Trends In Cord Blood Transplantationmentioning
confidence: 99%
“…In a systematic review that analyzed 104 donor‐transmitted cancers by renal graft, the most common types of transmitted cancer were renal cancer, melanoma, lymphoma, and lung cancer . In addition, there have been several reports about donor‐derived cancers (de novo cancers developing in transplanted donor cells) …”
Section: Introductionmentioning
confidence: 99%